1995
DOI: 10.1074/jbc.270.45.26762
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Expression of a Human Y4 Subtype Receptor for Pancreatic Polypeptide, Neuropeptide Y, and Peptide YY

Abstract: The pancreatic polypeptide family includes pancreatic polypeptide (PP), neuropeptide Y (NPY), and peptide YY (PYY). Members of the PP family regulate numerous physiological processes, including appetite, gastrointestinal transit, anxiety, and blood pressure. Of the multiple Y-type receptors proposed for PP family members, only the Y1 subtype has been cloned previously. We now report the cloning of an additional Y-type receptor, designated Y4, by homology screening of a human placental genomic library with tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
195
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(203 citation statements)
references
References 32 publications
6
195
0
2
Order By: Relevance
“…6 Both peptides are thought to bind to the hypothalamic Y-family receptors. PP binds primarily to the Y4 receptor 7 and PYY 3À36 binds predominantly to the Y2 receptor. 8 In addition to their central actions, PP and PYY may also inhibit food intake through a reduction in gut motility.…”
Section: Introductionmentioning
confidence: 99%
“…6 Both peptides are thought to bind to the hypothalamic Y-family receptors. PP binds primarily to the Y4 receptor 7 and PYY 3À36 binds predominantly to the Y2 receptor. 8 In addition to their central actions, PP and PYY may also inhibit food intake through a reduction in gut motility.…”
Section: Introductionmentioning
confidence: 99%
“…NPY is one of the most abundant neurohormones in the mammalian peripheral and central nervous systems. Receptor competition binding studies using analogs or segments of NPY, PYY and PP revealed that at least four receptor subtypes (YI, Y2, Y3, Y4) exist [4,5]. The Y1, Y2, and Y4 receptors have been cloned recently and it could be shown that they all belong to the G-protein coupled receptor family.…”
Section: Introductionmentioning
confidence: 99%
“…The Y1, Y2, and Y4 receptors have been cloned recently and it could be shown that they all belong to the G-protein coupled receptor family. Whereas NPY shows high affinity to Y1 and Y2 receptors, PP is supposed to be the endogenous ligand of the Y4 receptor [5].…”
Section: Introductionmentioning
confidence: 99%
“…[25,26]. A putative Y 3 -receptor has been described only pharmacologically and no specific agonists or antagonists are known [27].…”
mentioning
confidence: 99%
“…Its wide range of action is exerted via several receptor subtypes, named Y 1 -[17±19], Y 2 -[20±22], Y 5 - [23] and y 6 - [24] receptor subtypes, whereas the related peptide PP binds to the Y 4 /PP 1 -receptor [25,26]. A putative Y 3 -receptor has been described only pharmacologically and no specific agonists or antagonists are known [27].…”
mentioning
confidence: 99%